63.6k views
4 votes
Solve the system of linear equations by substitution.
3x + y = -3 -2x + y =7

User Goldlife
by
4.1k points

2 Answers

14 votes
both equations are equal to 0
User Tstirrat
by
4.8k points
3 votes

Answer:

(-2, 3)

Explanation:

First solve one equation for y:


-2x+y=7\\y=7+2x

Now we can substitute this equation into the other one:


3x+7+2x=-3

Solve for x:


x=-2

Now substitute this value into the equation
y=7+2x:


y=7+2x(-2)

Solve for y:


7=3

Now your solution is (-2,3)

Hope this helps! :)

User Emmanuel Collin
by
4.5k points